2012
DOI: 10.1111/jvim.12006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Trial to Compare Vincristine and Vinblastine in aCOP‐Based Protocol for Lymphoma in Cats

Abstract: Background: Current standard chemotherapy protocols for lymphoma in cats carry risks of gastrointestinal toxicity, which can decrease quality of life and complicate response assessment. Protocols with less gastrointestinal toxicity may improve treatment tolerance.Hypothesis/Objectives: The study purpose was to compare response rate, outcome, and toxicity between cats that received vincristine or vinblastine as part of combination chemotherapy for lymphoma. We hypothesized that vinblastine would have similar ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 27 publications
(70 reference statements)
7
41
0
Order By: Relevance
“…Although no distinction was made between histologic types in the studies in the immediate post‐FeLV era, the alimentary form of lymphoma has historically accounted for the minority of cases, accounting for only 13–35% of the cases in studies published prior to 2005 . However, in studies published after 2005, there has been a steady increase in the intermediate‐ to high‐grade alimentary form, and it now accounts for 42–57% of the feline lymphoma cases seen . The study reported herein also has one of the highest reported percentages (63%) of the alimentary form of lymphoma, despite having excluded any small cell or low grade lymphoma cases.…”
Section: Discussionmentioning
confidence: 80%
“…Although no distinction was made between histologic types in the studies in the immediate post‐FeLV era, the alimentary form of lymphoma has historically accounted for the minority of cases, accounting for only 13–35% of the cases in studies published prior to 2005 . However, in studies published after 2005, there has been a steady increase in the intermediate‐ to high‐grade alimentary form, and it now accounts for 42–57% of the feline lymphoma cases seen . The study reported herein also has one of the highest reported percentages (63%) of the alimentary form of lymphoma, despite having excluded any small cell or low grade lymphoma cases.…”
Section: Discussionmentioning
confidence: 80%
“…Those with a lower body weight had an increased odds ratio of dying of their disease. Lower body weight has been previously shown to be associated with a poorer prognosis in a number of conditions . Unfortunately, the BCS was not available for a large number of the cats in the current study, so it is difficult to identify whether it was the thinner cats that had the poorer prognosis or just those with a smaller stature.…”
Section: Discussionmentioning
confidence: 99%
“…However, a negative association between weight loss before starting chemotherapy and the likelihood to achieve CR has previously been reported in cats . Additionally, two recent studies have shown the prognostic significance of baseline body weight and weight changes during the course of treatment of feline lymphoma . Exact reasons for the occurrence of anorexia not accompanied by vomiting in cats undergoing chemotherapy are difficult to elucidate; however, they may probably – as in humans – be associated with sustained nausea and with that considerably impact the individual's quality of life.…”
Section: Discussionmentioning
confidence: 99%